ANALISIS PENGETAHUAN IBU DENGAN KEBERHASILAN TOILET TRAINING ANAK USIA TODDLER (LITERATUR REVIEW STUDY) - KUSUMAWATI, SUSI DEWIASIH; PRATIWI, RITA DWI; CHINALDY, RIZKY; ROMLAH, SITI NOVY (Sekolah Tinggi Ilmu Kesehatan Widya Dharma Husada Tangerang, 2022)
ABSTRACTThe number of children under five in Indonesia is 30% of the 250 million Indonesian population and based on the National Household Health Survey (SKRT) the number of children under five who have difficulty controlling defecation and defecation at the age of up to preschool reaches 75 million children. Sources of article data were searched through databases, namely PubMed, garuda journal,